Is it the end of TILLING era in plant science? - Szurman-Zubrzycka, Miriam; Kurowska, Marzena; Till, Bradley J.; Szarejko, Iwona (Frontiers in Plant Science, 2023)
Since its introduction in 2000, the TILLING strategy has been widely used in plant research to create novel genetic diversity. TILLINGIt is based on chemical or physical mutagenesis followed by the rapid identification of mutations within genes of interest. TILLING mutants may be used for functional analysis of genes and because of being nontransgenic, they may be directly used in pre-breeding programs. Nevertheless, classical mutagenesis is a random process, giving rise to mutations all over the genome. Therefore TILLING mutants carry background mutations, some of which may affect the phenotype and should be eliminated, which is often time-consuming. Recently, new strategies of targeted genome editing, including CRISPR/Cas9-based methods, have been developed and optimized for many plant species. These methods precisely target only genes of interest and produce very few off-targets. Thus, the question arises: is it the end of TILLING era in plant studies? In this review, we recap the basics of the TILLING strategy, summarize the current status of plant TILLING research and present recent TILLING achievements. Based on these reports, we conclude that TILLING still plays an important role in plant research as a valuable tool for generating genetic variation for genomics and breeding projects.